Facile and convenient method for synthesis of aryl- and heteroaryl iodonium salts; Современные проблемы органической химии - Soldatova N. S. Nataliya Sergeevna; Kukurina O. S. Olga Sergeevna; Sukhorukova E. G. Ekaterina Georgievna; Postnikov P. S. Pavel Sergeevich; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich) (2017, 2017)
Title screen